KARIR LINTAS BATAS ORGANISASIONAL DAN KECOCOKAN KARIR (BOUNDARYLESS CAREER AND CAREER FIT) - Widianti, Emma (Fakultas Ekonomi - Universitas Setia Budi, 2019)
The purpose of this paper is to give a bridge in understanding the relationship between boundaryless careers and organizational or individual outcomes. Career fit is assumed to have closer relationship with boundaryless career before we can further explain those outcomes. This relationship is explained by using organizational and individual perspectives both externally and internally in four types of boundaryless careers (i.e., internal psychological, internal enacted, external psychological, and external enacted), and by considering individual characteristics (i.e.,knowledge worker and non-knowledge worker). Two propositions are offered, first, knowledge worker is more suitable (has career fit) with organizational career process focusing on external boundaries, second, non-knowledge worker is more fit with organizational career process focusing on internal boundaries. Both internal and external orientation will require HR to have relevant practices and policies to support those fit.